A Case of “Cryptammonia”: Disseminated Cryptococcal Infection Generating Profound Hyperammonemia in a Liver Transplant Recipient - Steven M. Phillips DO; Stephanie M. Pouch MD; Denise J. Lo MD; Sheetal Kandiah MD; Koba A. Lomashvili MD; Ram A. Subramanian MD; Peter Moran PharmD; Alley Killian PharmD; Prem A. Kandiah MD (Journal of Investigative Medicine High Impact Case Reports, 2022)
Mycoplasma and Ureaplasma infections have been described as a cause of hyperammonemia syndrome leading to devastating neurological injury in the post-transplant period, most commonly in lung transplant recipients. The occurrence of significant hyperammonemia caused by other urease-producing organisms remains unclear. We describe a case of disseminated cryptococcosis presenting with profound hyperammonemia in a 55-year-old orthotopic liver transplant recipient. Through a process of elimination, other potential causes for hyperammonemia were excluded revealing a probable association between hyperammonemia and disseminated cryptococcosis.